La jetée, Sans soleil two films by Chris Marker - Duncan, Trevor (The Criterion Collection, 2007)
An unnamed man experiments with time travel, in hopes of finding a solutions to the problems of his post-apocalyptic home era. Narrated almost entirely using black-and-white still photographs.
1.66:1 aspect ratio, 16:9. - New, restored high-definition digital transfers, approved by director Chris Marker
Orig.: Frankreich 1963
Enth. new video interview with filmmaker Jean-Pierre Gorin ; "Chris on Chris", a video piece on Marker by filmmaker and critic Chris Darke ; two excerpts from the French TV series "Court-circuit", directed by Luc Lagier: the first, a look at David Bowie's music video for "Jump they say", inspired by "La Jetée"; the second, an analysis of Hitchcock's "Vertigo" and its influence on Marker ; a booklet featuring a new essay by Marker scholar Catherine Lupton, an interview with Marker, and notes on the films and filmmaking by Marker
Keywords: Time travel -- Drama; Personal/independent works; Science fiction; Shorts